Peran Zakat Sebagai Salah Satu Upaya Pengentasan Kemiskinan - Andi Muhammad Rifqy Ramadhan; Dhiyan azizah; Kurniati (4, 2026)
Zakat is one of the pillars of Islam with multidimensional dimensions, encompassing spiritual, social, and economic aspects. From an Islamic philosophical perspective, zakat is not only viewed as a ritual obligation to purify wealth and the soul, but also as an instrument for wealth distribution oriented towards social justice and poverty alleviation. Ontologically, zakat is understood as a manifestation of faith and social solidarity of Muslims that serves to maintain a balance between individual and collective interests. Through the obligation of zakat, Islam emphasizes that wealth is not merely personal property, but also contains the rights of others that must be fulfilled to achieve social harmony. Epistemologically, this study uses a normative philosophical approach with a literature study method. The main sources of the study include the Qur'an, hadith, the thoughts of classical scholars, and contemporary literature that examines zakat, Islamic philosophy, and social justice. This approach allows for an in-depth analysis of the philosophical foundations of zakat, both in terms of its value and its purpose in the structure of social life. From an axiological perspective, this study confirms that zakat has multiple benefits. Theoretically, this research enriches the academic literature on Islamic philosophy and Islamic economic law, particularly regarding the relevance of zakat to the issue of global poverty. Practically, zakat is a strategic solution for reducing social inequality when managed professionally, responsibly, and transparently by a competent institution. Therefore, from an Islamic philosophical perspective, zakat is highly urgent as a pillar of the welfare of the people and an instrument for sustainable poverty alleviation. Abstrak Zakat merupakan salah satu rukun Islam yang memiliki dimensi multidimensional, mencakup aspek spiritual, sosial, dan ekonomi. Dalam perspektif falsafah Islam, zakat tidak hanya dipandang sebagai kewajiban ritual untuk menyucikan harta dan jiwa, tetapi juga sebagai instrumen distribusi kekayaan yang berorientasi pada keadilan sosial dan pengentasan kemiskinan. Secara ontologis, zakat dipahami sebagai manifestasi keimanan dan solidaritas sosial umat Islam yang berfungsi menjaga keseimbangan antara kepentingan individu dan kepentingan kolektif. Melalui kewajiban zakat, Islam menegaskan bahwa harta bukan sekadar milik pribadi, tetapi terdapat hak orang lain di dalamnya yang harus ditunaikan demi terwujudnya harmoni sosial. Secara epistemologis, penelitian ini menggunakan pendekatan normatif-filosofis dengan metode studi pustaka. Sumber utama kajian mencakup Al-Qur’an, hadis, pemikiran para ulama klasik, serta literatur kontemporer yang mengkaji zakat, filsafat Islam, dan keadilan sosial. Pendekatan ini memungkinkan analisis mendalam mengenai landasan filosofis zakat, baik dari aspek nilai maupun tujuannya dalam struktur kehidupan sosial. Dari sudut pandang aksiologi, kajian ini menegaskan bahwa zakat memiliki manfaat ganda. Secara teoritis, penelitian ini memperkaya khazanah akademik mengenai filsafat Islam dan hukum ekonomi Islam, khususnya terkait relevansi zakat terhadap isu kemiskinan global. Secara praktis, zakat merupakan solusi strategis dalam mengurangi ketimpangan sosial apabila dikelola secara profesional, amanah, dan transparan oleh lembaga yang kompeten. Dengan demikian, zakat dalam perspektif falsafah Islam memiliki urgensi tinggi sebagai pilar kesejahteraan umat sekaligus instrumen pengentasan kemiskinan yang berkelanjutan